Black Swans, The Day After e Desenvolvimento Territorial: ‘Revisitar’ e Aprender com Acção Experimental em Projectos de Investigação do CET e do D’C - Henriques, J. M. (Conferência 'Entre Transições' do Dinâmia-CET IUL, 2021)
In contemporary conditions, the probability of occurring events with potential harming effects that cannot be anticipated is increasing (pandemia, weather-related extreme events, financial instability, geo-political conflicts, etc.). Paradoxically, the probability of its occurrence is increasing but their occurrence cannot be anticipated. These kinds of events were already coined as “Black Swans” (Taleb 2012). They represent major challenges to territorial development planning and the production of adequate scientific contributions involves relevant challenges. The contribution of past experience of research projects developed in the framework of CET and D’C will be ‘revisited’ and their potential contributions analyzed on the basis of assumptions based on critical realism and philosophical pragmatism.